2014
DOI: 10.1080/10601325.2014.976748
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Deblocking Studies of Low Temperature Heat-Curable Blocked Polymeric Methylene Diphenyl Diisocyanates

Abstract: One package heat curable polyurethane system typically requires blocked isocyanates with a relatively low deblocking temperature. In this study, a series of new aromatic secondary amines blocked polymeric methylene diphenyl diisocyanate (pMDI) was synthesized and characterized. Hot-stage FTIR, DSC and TGA spectroscopic methods were used to determine the deblocking temperatures of the blocked isocyanates. Cure reaction between the blocked isocyanates and a commercial polyl (PPG-2000) were carried out to establ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…SEM analysis shows that AMT only partially coated on the cloth. On the other hand, for the MMT coatings (Figure d), the isocyanate groups on MMT build carbamate linkage with hydroxyl groups on the cotton cloth during the coating process; ,, therefore, a smooth MMT coating is formed over the cotton fiber surfaces.…”
Section: Resultsmentioning
confidence: 99%
“…SEM analysis shows that AMT only partially coated on the cloth. On the other hand, for the MMT coatings (Figure d), the isocyanate groups on MMT build carbamate linkage with hydroxyl groups on the cotton cloth during the coating process; ,, therefore, a smooth MMT coating is formed over the cotton fiber surfaces.…”
Section: Resultsmentioning
confidence: 99%
“…Along with aliphatic TPU, aromatic diisocyanates such as 4,4′-diphenylmethane diisocyanate (MDI), 2,4-toluylene diisocyanate (TDI), and cycloaliphatic isophorone diisocyanate (IPDI) may be used for the synthesis of TPUs. The symmetrical structure of the aromatic MDI is such that a strong degree of phase separation is achieved between the soft and hard segments, especially at low temperatures [110]. This leads to a regular morphology and consequently high mechanical and adaptive properties of polyurethane materials.…”
Section: Structure Of Thermoplastic Polyurethanesmentioning
confidence: 99%
“…When investigating imidazole blocked poly(MDI) FTIR analysis produced a deblocking temperature of 170°C, considerably lower than that produced by TGA (216°C) and 120°C lower than that produced by DSC (291°C). 64 Furthermore, Gedan-Smolka et al reported differences in deblocking temperature when probing hydroxybenzoic acid ethyl ester blocked HDI. Analysis using FTIR afforded a deblocking temperature of 118°C, yet analysis using simultaneous thermal analysis coupled with a quadrupole mass spectrometer (STA-QMS) revealed three deblocking temperatures (DSC/TGA = 150°C, DSC = 170°C and MS = 155°C), all of which were significantly higher than that produced by FTIR.…”
Section: And 63mentioning
confidence: 99%
“…Imidazole/imidazoline Imidazole 64,86 Basicity of imidazole able to accelerate the blocking reaction without additional catalyst. 22 Large substituent effect on deblocking temperature.…”
Section: -145 N-hydroxyphthalimide 85mentioning
confidence: 99%
See 1 more Smart Citation